Developing Kenjeran as a Tourism Destination Based on Fisher Community Approach - Yunita, Febri Rizma; Suharto, Bambang; Isnaini, Santi (Lasigo Akademia Indonesia, 2024)
Kenjeran has strengths in the fisheries sector which has great potential to be developed as tourism with unique culinary delights, considering the abundant diversity of processed seafood. This research aims to explore opportunities for developing Kenjeran using Community-Based Tourism (CBT) theory and the 4A components, namely Attraction, Accessibility, Amenity, Ancillary. The method used in this research is a qualitative method with thematic analysis and SWOT analysis. The results of this research indicate that Kenjeran has implemented community-based tourism. However, it remains at the fifth level, namely approval, as the extent of citizen participation in decision-making is still not entirely clear. Meanwhile, the results of the SWOT analysis show that the location of the quadrant point is in a very profitable aggressive strategy (growth-oriented strategy) position. This strategy can focus on increasing local community participation, particularly through education in tourism management and governance, ensuring the fishermen’s active involvement in decision-making processes. The active fishing community is positioned as a central element in managing tourism activities, such as culinary tourism and maritime festivals. In addition, external threats like competition from other destinations and environmental concerns are addressed by adopting sustainable tourism practices, including eco-tourism and infrastructure development aligned with environmental conservation principles.